PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PENGARUH GLOBALISASI DENGAN MODEL DISCOVERI LEARNING PADA SISWA KELAS IV SD KRISTEN KAIWATU - Serna, Welhemina Yermina; Johannes, Nathalia Y.; Septory, Jekriel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the improvement in learning outcomes of material on the effects of globalisation through the discovery learning model in Grade IV students at Kaiwatu Christian Primary School. The research method used was classroom action research, with the subjects being 22 Grade IV students at Kaiwatu Primary School. The results of the study show that based on the research results, the test scores obtained by students increased, namely the average initial test score of 40 increased in cycle I after the teacher used the discovery learning model in teaching with an average score of 60. Student learning outcomes improved in cycle II, with the average score increasing to 78. In addition to student learning outcomes, the results of observations and interviews also showed that, in general, students and teachers were very interested in the use of the discovery learning model in PKN learning in the fourth grade of SD Kaiwatu.